Pleistocene amphibians and squamates from the Upper Jordan Rift Valley, Gesher Benot Ya'aqov and Nahal Mahanayeem Outlet (MIS 20–18 and MIS 4/3). Issue 1 (15th October 2018) - Biton, Rebecca; Bailon, Salvador; Goren-Inbar, Naama; Sharon, Gonen; Rabinovich, Rivka
ABSTRACT: The Acheulian site of Gesher Benot Ya'aqov (GBY) and the Mousterian site of Nahal Mahanayeem Outlet (NMO) are open-air sites situated on the bank of the Upper Jordan River at its southern estuary in the Hula Valley, Israel. Both sites were deposited on the shore of a paleo-Lake Hula, a shallow body of water that persisted throughout a considerable part of the Pleistocene as a fresh-water lake. Most of the amphibian and squamate taxa recovered are aquatic species related to the natural biota of the Hula Valley, alongside some terrestrial species. Twelve amphibian and squamate taxa were recovered at each site. Most of the species recovered from the archaeological contexts do not differ from extant Hula Valley amphibians and squamates, with the exception of a varanid ( Varanus sp.) recovered at GBY and the possible presence of the eastern fourlined ratsnake (cf. Elaphe sauromates ). The snake's presence could indicate slightly cooler conditions during human occupation at NMO. A noteworthy continuity in species presence is observed throughout the many archaeological horizons as well as in comparison to the current Hula basin fauna. This suggests a surprising similarity in environmental conditions over a significant portion of the Quaternary in this region.